Advanced smart computing technologies in cybersecurity and forensics - Kaushik, Keshav; Tayal, Shubham; Bhardwaj, Akashdeep; Kumar, Manoj (CRC Press, Taylor & Francis Group, 2022)
This book addresses the topics related to artificial intelligence, the Internet of Things, blockchain technology, and machine learning. It brings together researchers, developers, practitioners, and users interested in cybersecurity and forensics. The first objective is to learn and understand the need for and impact of advanced cybersecurity and forensics and its implementation with multiple smart computational technologies. This objective answers why and how cybersecurity and forensics have evolved as one of the most promising and widely-accepted technologies globally and has widely-accepted applications. The second objective is to learn how to use advanced cybersecurity and forensics practices to answer computational problems where confidentiality, integrity, and availability are essential aspects to handle and answer. This book is structured in such a way so that the field of study is relevant to each readers major or interests.
Keywords: Aufsatzsammlung